2011
DOI: 10.1002/jwmg.172
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among deer in a chronic wasting disease endemic zone

Abstract: Although it is known that chronic wasting disease (CWD) can be transmitted by both direct animal-to-animal contact and contact with contaminated environments, the relative role of each mechanism in the spread of CWD in free-ranging populations has yet to be defined. We investigated patterns of interaction between mule deer (Odocoileus hemionus) in order to understand how factors such as season and landscape may influence patterns of disease spread in these populations. Using location data from male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
24
1
Order By: Relevance
“…Mule deer have a marked right-skewed distribution of group sizes [25] with obvious seasonality driven by environmental conditions and reproductive behaviour [25, 28–31]. The largest mixed-sex groups are observed in winter, while the smallest are seen during the fawning period [25, 29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mule deer have a marked right-skewed distribution of group sizes [25] with obvious seasonality driven by environmental conditions and reproductive behaviour [25, 28–31]. The largest mixed-sex groups are observed in winter, while the smallest are seen during the fawning period [25, 29].…”
Section: Introductionmentioning
confidence: 99%
“…The largest mixed-sex groups are observed in winter, while the smallest are seen during the fawning period [25, 29]. In our study area, open flat habitat is associated with larger groups and a greater frequency of close proximity events (deer within 25 m of each other), while rugged terrain is used by many individuals in small groups [25, 28]. …”
Section: Introductionmentioning
confidence: 99%
“…A study on chronic wasting disease (CWD) transmission dynamics was conducted at Antelope Creek (50.66°N, 108.27°W), a 248 km 2 CWD endemic area in south Saskatchewan, Canada (Silbernagel 2011;Mejía Salazar et al 2016). This study site is within the mixed grassland ecoregion and consists of crop (46.6%), grassland (35.6%), shrub (7.6%), woodland (2%) and open water (0.3%).…”
Section: Data Sourcementioning
confidence: 99%
“…8,9 Therefore, soil properties are an important factor for PrP TSE preservation and transmission in the environment. [10][11][12][13] Analysis of soil-prion interactions and the impact on infectivity is a complicated task because soils are multicomponent systems consisting of mineral particles (clay, silt, sand); soil organic matter (humic, fulvic acids and humin); humus or/and Fe-Mn films and cutans interacting with mineral particles. The enormous complexity of soils indicates a need to examine a variety of soils and their separated compounds (mineral and organic) to identify the ability of prions to bind the soil, what the effect of binding is on infectivity and what components of soil bind prions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in southern Saskatchewan has suggested the importance of landscape position for CWD transmission: croplands have a higher risk compared with coulees and creek valleys. 13 This correlation may be related to soil properties because soil texture, organic matter content, pH etc. usually vary with topography.…”
Section: Introductionmentioning
confidence: 99%